Mysterious Virus Nipah: A Comprehensive Review - Bidduth Kumar Sarkar; Alam Khan; Bithe Saha; Susmoy Sarker; Farjana Akter; Barno Kumar Sarkar; Tanvir Ahmed; Sukalyan Kumar Kundu (National Journal of Community Medicine)
Nipah virus is regarded as one of the most notorious and infectious viruses in the world with high mortality. This narrative literature review aims to offer basic information on the epidemiology, transmission methods, pathophysiology, treatment plan, diagnostic techniques, prevention about Nipah Virus those have been published using the digital repositories such as PubMed and Google Scholar. Results of reviewing relevant articles demonstrated that six hundred fifty (around 700) confirmed human cases of infections due to this virus were reported up until 2023. Between January 4 and February 13, 2023, seven districts in two divisions of Bangladesh (where outbreaks happen almost annually) experienced 73% case fatality rate and in 2024, again Bangladesh faced 100% mortality rate which is alarming issue in concern. The first infection case was recorded in Malaysia in 1998 with a mortality rate of close to 40%. Further outbreaks of the disease have occurred in different countries, particularly in South and Southeast Asia, over two decades later with a mortality rate above 50%. Specially in India, mortality rate reaches to its peak (100%) in two distinct areas in 2007 and 2021. Researchers from around the world are focusing on creating an effective vaccine, advanced diagnostic methods such as CRISPR-based techniques and active therapeutics due to its high pathogenicity in people and the absence of any treatment methods to combat it. Throughout history, viral outbreaks of different frequency and severity have wreaked misery all across the world and the Covid-19 worldwide pandemic provided an example of this type of scenario.